Antimicrobial Therapy in Preventing Wound Infection Following Appendectomy for Uncomplicated Appendicitis in Children : Comparison Between Single Dose and Multiple Doses - Rahman, MA Mushfique; Farooq, Md Abdullah Al; Bhuiyan, Md Akbar Husain; Sajid, Md Minhajuddin; Chowdhury, Tanvir Kabir; Islam, M Kabirul (Journal of Chittagong Medical College Teachers' Association, 2012)
The role of antibiotics in acute appendicitis is well established. If there is no intra-peritoneal contamination the antibiotic administration should be prophylactic. The current trend is to continue post operative antibiotics for fixed periods ranging from 5 to 7 days in most of the hospitals in our country. Our aim was to assess the safety in relation to wound infection after appendectomy for uncomplicated appendicitis in children with single dose combined antimicrobial therapy and multiple doses. For this purpose a prospective comparative study was done in department of surgery, Dhaka Shishu Hsopital from January, 2004 to December, 2004. Children upto 12 yrs of age with diagnosis of uncomplicated appendicitis were included in this study and preoperative findings of perforated, gangrenous appendix, histopathological report of normal appendix were excluded. Patients received antibiotics prior to hospital admission and acute appendicitis with other systemic diseases were also excluded. Total 60 patients were selected randomly in control (30 patients) and study (30 patients) group. All patients received per operative triple untibiotic therapy (Amoxycillin, Metronidazole and Gentamicin). No further antibiotic were given in study group, post operative antibiotics were continued for 7 days in control group. Wound infection was noted in 1 patient (3.33%) of each group and cost of antibiotics was significantly higher in control group (P value > 0.05). It has proved that uncomplicated appendicitis in children can be treated safely with single dose triple antibiotic therapy and use of extended period of post operative antibiotics gives no added benefit. JCMCTA 2012; 23(1): 26-30